Development of Project-based Blended Learning (PjB2L) Model To Increase Pre-Service Primary Teacher Creativity - Wahyudi Wahyudi; Adi Winanto (Universitas Negeri Makassar, 2018)
One of the aims of Indonesian education is to develop the potential of learners to become creative human beings. It takes a creative teacher to meet this need. Not just teaching, but teachers who are able to teach with innovative models, strategies and methods provide an opportunity for students to be skilled from creative products including in the field of mathematics in elementary school (SD). The aim of this research is to develop model to grow pre-service primary teacher students’ creativity in designing the lesson plan. The method used in this research was R&D with ASSURE development model. Product validation was done through an expert’s assessment by using the expert’s validation sheet. Product effectiveness was seen by implementing limited development testing to a particular class with a one group pretest-posttest design and the result was analyzed by using a Paired-Samples T-Test. The result of this research was a project-based e learning model to increase the creativity of pre-service primary teacher college students in designing a lesson plan. The validity of the learning model was proven by the result of the expert assessment in learning (face-to-face and online), material and instructional media. This model is also effectively usable in instructions to produce creative lesson plans for teaching Elementar School Mathematics as it is shown by the difference in the average pretest and posttest scores with sig. (2-tailed) 0,000.